2020
DOI: 10.1016/j.ijantimicag.2020.106077
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid therapy for patients with COVID-19 pneumonia: a before–after study

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 9 publications
2
29
0
1
Order By: Relevance
“…Consistent with this recommendation, dexamethasone has been recently shown to lower COVID-19 28-day mortality only among patients who were receiving respiratory support [ 30 ]. However, a study with some limitations has showed that prednisone or methylprednisolone was associated with a significant reduction in COVID-19 hospital mortality and recommended initiation of clinical trials testing corticosteroids during the inflammatory phase of COVID-19 [ 31 ]. Similarly, 40–80 mg/d (0.75–1.5 mg/kg/d) of methylprednisolone for 3 days, tapered to 20 mg/d, with a total treatment period of less than 7 days benefited COVID-19 patients with marked radiologic progression and LDH levels of less than two times the upper limit number and a tailored individualized course was suggested as rescue treatment in more severe or critically ill patients [ 32 ].…”
Section: Glucocorticoids Role In Treatment Of Covid-19mentioning
confidence: 99%
“…Consistent with this recommendation, dexamethasone has been recently shown to lower COVID-19 28-day mortality only among patients who were receiving respiratory support [ 30 ]. However, a study with some limitations has showed that prednisone or methylprednisolone was associated with a significant reduction in COVID-19 hospital mortality and recommended initiation of clinical trials testing corticosteroids during the inflammatory phase of COVID-19 [ 31 ]. Similarly, 40–80 mg/d (0.75–1.5 mg/kg/d) of methylprednisolone for 3 days, tapered to 20 mg/d, with a total treatment period of less than 7 days benefited COVID-19 patients with marked radiologic progression and LDH levels of less than two times the upper limit number and a tailored individualized course was suggested as rescue treatment in more severe or critically ill patients [ 32 ].…”
Section: Glucocorticoids Role In Treatment Of Covid-19mentioning
confidence: 99%
“…In 29 studies the dose of corticosteroids was reported: In 16 studies an equivalent dose of > 1 mg/kg prednisolone was used [37][38][39]41,43,44,[48][49][50][51]53,54,[56][57][58]64] and in 11 studies a lower equivalent dose than 1 mg/kg prednisolone [23,[34][35][36]40,42,47,52,62,63,65]. In two studies a low and high dose group were present [45,46].…”
Section: Corticosteroid Regimen (Table 1 and Appendix 6)mentioning
confidence: 99%
“…The effect of corticosteroids on oxygenation was very heterogeneous: In four studies there was no signi cant effect [41,42,51,55], in three studies signi cant improvement was described [50,60,64] and in four studies worse outcome was observed. [35,39,54,57] Six studies addressed secondary infections. More frequently broad spectrum antibiotics were used in de corticosteroid group [39,47,53] and more secondary infections/sepsis episodes were described [35,36].…”
Section: Effect Of Steroids On Primary and Secondary Outcomes (Table mentioning
confidence: 99%
See 1 more Smart Citation
“…With much lower HCQ usage, a similar pre/post study ( Table 1 ( Bani-Sadr et al, 2020 )) found steroid-associated reduced mortality, but only after multivariate adjustment. These studies support the early combined in-hospital use of HCQ and MPD to reduce mortality and the need for ventilation.…”
mentioning
confidence: 88%